Zooplankton of Cat Dam Lake (Malatya-Turkey) with a new record for Turkish rotifers Lecane intrasinuata (Olofsson, 1917) - Saler, S.; Bulut, H.; Karakaya, G. (Iranian Fisheries Science Research Inst-Ifsri, 2019)
[Abstract Not Available]
Keywords: Rotifera; Lecane intrasinuata; New record; Turkey; Cat Dam Lake